2011
DOI: 10.1109/tit.2010.2090234
|View full text |Cite
|
Sign up to set email alerts
|

Convex Programming Upper Bounds on the Capacity of 2-D Constraints

Abstract: Abstract-The capacity of 1-D constraints is given by the entropy of a corresponding stationary maxentropic Markov chain. Namely, the entropy is maximized over a set of probability distributions, which is defined by some linear requirements. In this paper, certain aspects of this characterization are extended to 2-D constraints. The result is a method for calculating an upper bound on the capacity of 2-D constraints.The key steps are: The maxentropic stationary probability distribution on square configurations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…There are recent efforts in obtaining bounds by linear programming and convex programming for the bit-stuffing algorithms on various applications (see e.g., [21], [22]). It would be of interest to apply their approaches to obtain tight bounds for our setting.…”
Section: Resultsmentioning
confidence: 99%
“…There are recent efforts in obtaining bounds by linear programming and convex programming for the bit-stuffing algorithms on various applications (see e.g., [21], [22]). It would be of interest to apply their approaches to obtain tight bounds for our setting.…”
Section: Resultsmentioning
confidence: 99%
“…In general, due to the high computational complexity, few studies have been conducted to obtain tight bounds on the capacity of 2-D channels with memory, except for the capacity of some special 2-D constraints. Specifically, the lower bounds on the capacity of some 2-D constraints were presented and analyzed in [15]- [17], based on either bit-stuffing encoders or tilling encoders; and the upper bounds were provided by Forchhammer and Justesen [18], Tal and Roth [19].…”
Section: Channels With 2-d Crosstalkmentioning
confidence: 99%
“…We then extend the idea for the 1-D case to compute an upper bound on the capacity for the 2-D case. In [19], it was demonstrated that there exists a stationary and symmetric input distribution that achieves the capacity of some special 2-D constraints. In fact, we can prove that this conclusion also holds for optical on-off-keying channels with 2-D crosstalk.…”
Section: Channels With 2-d Crosstalkmentioning
confidence: 99%
“…In this figure, the vertex i is marked as a gray square; D i is indicated by the black vertices that the vertex i depends on; the stationary constraint is applied to the region T that includes all the vertices plotted. Based on these schemes, we get the lower bounds for the capacities, which are given in the second column in Table I. 3) Upper Bound based on Convex Programming: In [6], convex programming was used as a method for calculating an upper bound on the capacity of 2-D constraints. The idea is based on the observations that there exists an optimal distribution θ * such that θ * is stationary and symmetric when the array is sufficiently large.…”
Section: ) Lower Bound Based On Bit-stuffingmentioning
confidence: 99%
“…For a rectangular array, if two sets of vertices A and B are reflection symmetric about a horizontal/vertical line or a 45-degree line, then they have the same state (configuration) distribution. Note that the reflection symmetry about a 45-degree line is also called transposition invariance in [6]. For a triangular array, there are more symmetries: if two sets of vertices A and B are reflection symmetric about a horizontal/vertical line or a 30/60-degree line, then they have the same state (configuration) distribution.…”
Section: ) Lower Bound Based On Bit-stuffingmentioning
confidence: 99%